Finding the way forward for forensic science in the US—A commentary on the PCAST report. (September 2017) - Evett, I.W.; Berger, C.E.H.; Buckleton, J.S.; Champod, C.; Jackson, G.
Highlights: A response to the PCAST report on the future of forensic science. We reject the PCAST vision of the scientist as a "black-box". We strongly favour the notion of calibration of expert opinion. We explain errors of reasoning and sources of confusion in the PCAST report. Our paradigm is scientific judgement founded on logic and reliable knowledge. Abstract: A recent report by the US President's Council of Advisors on Science and Technology (PCAST), (2016) has made a number of recommendations for the future development of forensic science. Whereas we all agree that there is much need for change, we find that the PCAST report recommendations are founded on serious misunderstandings. We explain the traditional forensic paradigms of match and identification and the more recent foundation of the logical approach to evidence evaluation. This forms the groundwork for exposing many sources of confusion in the PCAST report. We explain how the notion of treating the scientist as a black box and the assignment of evidential weight through error rates is overly restrictive and misconceived. Our own view sees inferential logic, the development of calibrated knowledge and understanding of scientists as the core of the advance of the profession.